2018
DOI: 10.1007/s11139-018-9993-y
|View full text |Cite
|
Sign up to set email alerts
|

Complete p-elliptic integrals and a computation formula of $$\pi _p$$ π p for $$p=4$$ p = 4

Abstract: The complete p-elliptic integrals are generalizations of the complete elliptic integrals by the generalized trigonometric function sin p θ and its half-period π p . It is shown, only for p = 4, that the generalized p-elliptic integrals yield a computation formula of π p in terms of the arithmetic-geometric mean. This is a π p -version of the celebrated formula of π, independently proved by Salamin and Brent in 1976.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In [1], properties of the extended generalized Mittag-Leffler function are studied in details, and it is given that E γ,δ,k,c μ,α,l (t; p) is absolutely convergent for k < δ + R(μ). For other recent results see [15,37,38,46]. Let S be the sum of series of absolute terms of E γ,δ,k,c μ,α,l (t; p), then we have E γ,δ,k,c μ,α,l (t; p) ≤ S. We will use this property of extended generalized Mittag-Leffler function in sequel.…”
Section: Introductionmentioning
confidence: 97%
“…In [1], properties of the extended generalized Mittag-Leffler function are studied in details, and it is given that E γ,δ,k,c μ,α,l (t; p) is absolutely convergent for k < δ + R(μ). For other recent results see [15,37,38,46]. Let S be the sum of series of absolute terms of E γ,δ,k,c μ,α,l (t; p), then we have E γ,δ,k,c μ,α,l (t; p) ≤ S. We will use this property of extended generalized Mittag-Leffler function in sequel.…”
Section: Introductionmentioning
confidence: 97%
“…In the past few centuries, the complete elliptic integrals of the first and second kinds K(r) and E(r), defined on [ have been found that they have many important applications in mathematics as well as in physics and engineering, including the evaluation of the length of curves [1,5,9,10,22,28,39,42,46,55], the algorithm of the circumference ration π [11,13,21,41], the computations of electromagnetic field and the study of the period of the simple pendulum [12,15,19,25,30]. In 1990s, the complete elliptic integrals K(r) and E(r) appeared in geometric function theory frequently, especially in conformal and quasiconformal mappings [3,4,6,17,27,31,38,54,59].…”
Section: Introductionmentioning
confidence: 99%
“…is known as the generalized sine function with two parameters p, q > 1 in the literature (see, [9,10,14,21,24,[28][29][30]), and defined as the inverse function of…”
Section: Introductionmentioning
confidence: 99%